(untitled) (The Review of Diabetic Studies, 2025)
Background: Uterine Leiomyoma is the most common benign tumors affecting women of reproductive age with a prevalence rate of 20-40% in a 14-45 years age. Based on pathogenesis and clinical manifestation, Leiomyoma uterus can be correlated with Garbhashaya Granthi as granthi is referred as localized nodular swelling, relative hard in consistency. Patient information: We report a series of three cases presented to the OPD with AUB, diagnosed with Leiomyoma measuring <5cm on ultrasonography, and seeking non-surgical intervention for the management of the leiomyoma uterus. Per vaginal examination revealed Bulky Uterus in all cases. Intervention and Results: Management strategy adopted was Shodhana karma -Virechana followed by Shamana therapy with Shigrudi Yoga, Kanchanara Guggulu and Punarnavasava. The primary mechanism of action considered was Lekhana, Shothahara, and Granthihara karma. Cases showed >20% reduction in volume of Uterine Leiomyoma, all three cases with significant improvement in subjective parameters of menstrual abnormalities, abdominal pain, pressure symptoms and backache. Conclusion: This case series suggests that combining Virechana with specific Ayurvedic formulations may offer a safe, non-invasive option for small uterine leiomyomas. Larger clinical studies are needed to confirm these findings.